Abrasion-resistant and tear-resistant foam flame composite fabric and preparation method thereof
Patent Information
- Application Number
- CN202510498005.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-21
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-04-21
AI Technical Summary
[0005]有鉴于此,本发明的目的在于提出一种耐磨抗撕裂泡棉火焰复合面料及其制备方法,以解决现有技术中界面结合强度低、抗撕裂能力弱与碳纤维与聚氨酯基体界面相容性差的问题
本发明采用火焰活化工艺对硅烷长链改性聚氨酯泡棉进行表面处理,通过高温短时灼烧,显著提高其与聚酯纤维、聚氨酯薄膜的界面粘接强度,同时结合三嗪改性高强度聚酯纤维织物与碳纤维改性聚氨酯薄膜,最终复合面料的界面剥离强度与耐磨性提高。
Smart Images

Figure CN120382704B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of textile fabrics, and more particularly to a wear-resistant and tear-resistant foam flame composite fabric and its preparation method. Background Technology
[0002] In the textile industry, abrasion-resistant and tear-resistant composite fabrics are widely used in outdoor equipment, automotive interiors, industrial protective clothing and other fields due to their high durability requirements in extreme environments. Traditional composite fabrics are mostly made by bonding polyester fibers with polyurethane foam or film through hot pressing or adhesive bonding processes. However, with the diversification of application scenarios, existing technologies have exposed a series of key defects.
[0003] In existing technologies, traditional foam composite fabrics are usually made of polyester fiber as the base material, combined with polyurethane foam or film, and are composited by hot pressing or adhesive bonding process. The interfacial bonding strength is low, and delamination or edge tearing is prone to occur after long-term use. At the same time, although silane coupling agent treatment can improve interfacial compatibility, its short chain structure is prone to hydrolysis failure. Although carbon fiber reinforced polyurethane film can improve mechanical properties, the interfacial compatibility between carbon fiber and polyurethane matrix is poor, and stress concentration points are prone to occur, resulting in insufficient peel strength.
[0004] Therefore, based on the relevant technologies mentioned above, there is an urgent need to develop a wear-resistant and tear-resistant foam flame composite fabric and its preparation method. Summary of the Invention
[0005] In view of this, the purpose of this invention is to propose a wear-resistant and tear-resistant foam flame composite fabric and its preparation method, so as to solve the problems of low interfacial bonding strength, weak tear resistance and poor interfacial compatibility between carbon fiber and polyurethane matrix in the prior art.
[0006] To achieve the above objectives, the present invention provides a wear-resistant and tear-resistant foam flame composite fabric and its preparation method.
[0007] A wear-resistant and tear-resistant foam flame composite fabric comprises the following components in parts by weight: 35-45 parts modified high-strength polyester fiber fabric, 20-30 parts modified polyurethane film, 30-40 parts modified polyurethane foam, and 3-5 parts polyurethane hot melt adhesive.
[0008] A method for preparing a wear-resistant and tear-resistant foam flame-retardant composite fabric, comprising the following steps: Step S1: The modified polyurethane foam is calcined with a propane-oxygen mixed flame, heated to 800-1000℃, with a flame sweeping time of 1-3s / time and a melting depth ≤0.1mm, to obtain flame-activated foam. Step S2: Coat the modified high-strength polyester fiber fabric with polyurethane hot melt adhesive, then align the modified polyurethane film, place it on a hot press roller, heat to 110-130℃, pressure 0.5-1MPa, roller speed 3-5m / min, to obtain the pre-composite fabric. Step S3: Align and bond the flame-activated foam with the pre-composite fabric, let stand for 3-5 seconds, then place it on the hot press roller, heat to 30-50℃, pressure 1.5-2MPa, roller speed 5-10m / min, to obtain wear-resistant and tear-resistant foam flame-composite fabric. The modified high-strength polyester fiber fabric is a triazine-modified high-strength polyester fiber fabric; The modified polyurethane film is a carbon fiber modified polyurethane film; The modified polyurethane foam is a silane long-chain modified polyurethane foam.
[0009] Preferably, the triazine-modified high-strength polyester fiber fabric is prepared by the following method: Step A1: Add cyanuric chloride, 4-(ethylene oxide-2-ylmethyl)benzene-1,2-diol, sodium hydroxide, and deionized water to acetone solvent, stir and react for 3-5 hours, filter, and distill under reduced pressure to obtain intermediate 1; Step A2: Add intermediate 1 to tetrahydrofuran solvent, mix well, then add 6-amino-1-hexanol, heat to 20-30℃, stir for 10-14h, and after the reaction is complete, distill under reduced pressure to obtain intermediate 2. Step A3: Mix intermediate 2 with terephthalic acid, heat to 220-240℃, react for 2-4 hours, add the catalyst tetrabutyl titanate, vacuum to 40-50 Pa, heat to 250-260℃, react for 1-2 hours, then heat to 270-280℃, react for 3-5 hours. After the reaction is complete, cool and granulate to obtain polyester chips. Step A4: Dry the polyester chips, put them into a spinning machine, heat them to 300-320℃, filter them, extrude them with a twin-screw extrusion pressure of 4-5MPa and a winding speed of 700-900m / min, then stretch them with a stretching machine with a total stretch ratio of 4-5, and weave them with an air-jet loom to obtain triazine modified high-strength polyester fiber fabric.
[0010] Triazine-modified high-strength polyester fiber fabrics introduce a triazine ring structure through the reaction of cyanuric chloride and epoxy groups, forming a UV absorption barrier to prevent fiber aging caused by long-term light exposure. At the same time, the rigid structure of the triazine ring increases the tensile strength of the fiber, significantly enhancing the tear resistance of the fabric.
[0011] Preferably, the mass ratio of cyanuric chloride, 4-(ethylene oxide-2-ylmethyl)benzene-1,2-diol, sodium hydroxide, and deionized water in step A1 is 1:4-4.2:1.2-1.4:5.5-6; The mass ratio of intermediate 1 to 6-amino-1-hexanol in step A2 is 1.8-2:1; The mass ratio of intermediate 2 to terephthalic acid in step A3 is 4-5:1.
[0012] Preferably, the carbon fiber modified polyurethane film is prepared by the following method: Step B1: Add carbon fiber to acetone solvent, heat to 50-60℃, react for 10-14 hours, after the reaction is complete, sonicate for 3-7 minutes, dry to obtain degummed carbon fiber. Step B2: Add the degummed carbon fiber to a 65% concentrated nitric acid solution, heat to 80-100℃, react for 110-130 min, adjust the pH to 7, add the cyclotriphosphazene-modified silane coupling agent, heat to 90-110℃, react for 1-3 h, rinse with boiling water, and obtain cyclotriphosphazene-modified silane coupling agent-modified carbon fiber. Step B3: Mix polyether polyols YD-4110, YD-889, YD-204, and YD-380 evenly, add foam stabilizer and antioxidant, and stir for 20-40 minutes to obtain component A; Step B4: Add polymethylene polyphenyl polyisocyanate to a beaker, heat to 50-70℃, preheat for 50-70 min, and obtain component B; Step B5: Add component A and component B to a beaker, heat to 30-50℃, react for 2-4 minutes, stir for 1-3 minutes, then add carbon fiber modified with cyclotriphosphazene-modified silane coupling agent, heat to 50-60℃, cure for 50-70 minutes, cool to 20-30℃, and let stand for 22-26 hours to obtain carbon fiber modified polyurethane film.
[0013] The use of cyclotriphosphazene-modified silane coupling agent has multiple active sites that can simultaneously bond hydroxyl groups on the carbon fiber surface to the polyurethane matrix, improving the interfacial peel strength. In addition, the synthesis process of this coupling agent does not require toxic solvents, has high reaction efficiency, and reduces VOC emissions, meeting the requirements of green manufacturing.
[0014] Preferably, the mass ratio of the degummed carbon fiber, concentrated nitric acid solution, and cyclotriphosphazene-modified silane coupling agent in step B2 is 1:9-11:0.02-0.04; In step B5, the mass ratio of component A, component B, and carbon fiber modified by cyclotriphosphazene-modified silane coupling agent is 1:1.0-1.2:0.02-0.04.
[0015] Preferably, the cyclotriphosphazene-modified silane coupling agent is prepared by the following method: Step C1: Under an argon atmosphere, hexachlorocyclotriphosphazene and hydroquinone were added to tetrahydrofuran solvent and stirred until homogeneous. Triethylamine was added, and the temperature was raised to 65-75℃. The mixture was stirred for 45-50 hours until the reaction was complete. The mixture was then cooled, filtered, distilled under reduced pressure, and recrystallized to obtain intermediate 3. Step C2: Add paraformaldehyde to tetrahydrofuran solvent, add CaH2, heat to 20-30℃, react for 20-40 min, then heat to 50-70℃, add N-[3-(trimethoxysilyl)propyl]ethylenediamine, heat to 75-85℃, add intermediate 3, react for 2-4 h, filter, and distill under reduced pressure to obtain cyclotriphosphazene modified silane coupling agent.
[0016] Preferably, the mass ratio of hexachlorocyclotriphosphazene, hydroquinone, and triethylamine in step C1 is 1:0.33-0.37:0.80-0.83; In step C2, the mass ratio of paraformaldehyde, CaH2, N-[3-(trimethoxysilyl)propyl]ethylenediamine to intermediate 3 is 0.43-0.47:0.45-0.49:1.65-1.70:1.
[0017] Preferably, the modified polyurethane foam is prepared as follows: Step D1: Add tetrahydroxymethyl phosphonium sulfate to diethylene glycol dimethyl ether solvent, heat to 20-25℃, add n-octadecyltrichlorosilane, heat to 50-60℃, react for 50-70 min, heat to 120-140℃, react for 8-10 h, cool, crystallize, filter, and obtain cage-like quaternary phosphate long-chain organosilicon ester; Step D2: Under a nitrogen atmosphere, hexamethylene diisocyanate and polyether polyol LY-4110 are heated to 70-80℃ and reacted for 1-3 hours. The temperature is then lowered to 50-60℃, and chain extender diethylene glycol, catalyst stannous octoate and dibutyl dilaurate are added. The reaction is continued for 3-5 hours. Isocyanate trimer, cage-like quaternary phosphate long-chain organosilicon ester and chemically foamed microspheres are added. The mixture is stirred evenly and heated to 110-130℃ for 1-3 hours to obtain silane long-chain modified polyurethane foam.
[0018] By modifying polyurethane foam with long-chain silanes, the long-chain structure can penetrate deep into the polyurethane matrix to form physical entanglement. At the same time, the terminal silanol groups are chemically bonded to the fiber and film surface, significantly improving the interfacial bonding strength. The hydrophobicity and hydrolysis resistance of long-chain silanes effectively resist the erosion of humid and hot environments, making them suitable for outdoor high-humidity scenarios.
[0019] The cage-like quaternary phosphate long-chain organosilicon ester is evenly distributed in the foam. When exposed to fire, it decomposes to generate a phosphate barrier layer, which increases the limiting oxygen index of the fabric. At the same time, the long-chain organosilicon structure of the quaternary phosphate can inhibit the adhesion of microorganisms, making it suitable for scenarios with strict hygiene requirements such as medical protection and automotive interiors.
[0020] Preferably, the mass ratio of tetrahydroxymethylphosphoric acid sulfate to n-octadecyltrichlorosilane in step D1 is 1:0.50-0.53; The mass ratio of hexamethylene diisocyanate, polyether polyol LY-4110, diethylene glycol, stannous octoate, dibutyl dilaurate, isocyanate trimer, cage-like quaternary phosphate long-chain organosilicon ester, and chemically foamed microspheres in step D2 is 1:12-14:1.3-1.5:0.1-0.3:0.1-0.2:2-4:0.5-0.7:0.7-0.9.
[0021] The beneficial effects of this invention are: This invention employs a flame activation process to surface-treat silane long-chain modified polyurethane foam. Through high-temperature short-time calcination, the interfacial adhesion strength between the foam and polyester fibers and polyurethane films is significantly improved. Simultaneously, by combining triazine-modified high-strength polyester fiber fabric and carbon fiber-modified polyurethane film, the interfacial peel strength and abrasion resistance of the final composite fabric are improved.
[0022] This invention employs a staged hot-pressing process, with a low temperature during the pre-composite stage and an even lower temperature during the final composite stage. Combined with precise roller speed control, this effectively prevents the collapse of the closed-cell structure of the foam and reduces the risk of thermal damage to the surface carbon fiber film.
[0023] The flame activation and stepwise hot pressing process of this invention does not require complex equipment, and the reaction conditions are mild, reducing energy consumption. When produced on a large scale, the utilization rate of raw materials is improved and the overall cost is reduced.
[0024] This invention, through innovative material modification and phased composite process design, significantly improves the interfacial bonding strength and durability of fabrics by combining flame activation and low-temperature composite processes compared with existing technologies. It also has outstanding advantages in achieving green manufacturing and can be widely used in high-value-added fields such as outdoor sports equipment, automotive interiors, and industrial protective clothing, with broad application prospects. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only for this invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a flowchart illustrating the preparation process of the high-strength polyurethane fiber in this invention. Figure 2 This is a flowchart illustrating the preparation route of carbon fiber modified with cyclotrionitrile-modified silane coupling agent in this invention. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.
[0028] Example 1: S1: Add 100g of cyanuric chloride, 400g of 4-(ethylene oxide-2-ylmethyl)benzene-1,2-diol, 130g of sodium hydroxide, and 550g of deionized water to acetone solvent, stir and react for 4h, filter, and distill under reduced pressure to obtain intermediate 1. S2: Add 180g of intermediate 1 to 100mL of tetrahydrofuran solvent, mix well, then add 100g of 6-amino-1-hexanol, heat to 25℃, stir and react for 12h. After the reaction is complete, distill under reduced pressure to obtain intermediate 2. S3: Mix 450g of intermediate 2 with 100g of terephthalic acid, heat to 230℃, react for 3h, add 5.5g of catalyst tetrabutyl titanate, vacuum to 45Pa, heat to 255℃, react for 1-2h, then heat to 275℃, react for 4h, the reaction is complete, cool and granulate to obtain polyester chips. S4: Dry the polyester chips, put them into a spinning machine, heat them to 310℃, filter them, extrude them with a twin-screw extrusion pressure of 4MPa and a winding speed of 800m / min, then stretch them with a stretching machine with a total stretch ratio of 4.5, and weave them with an air-jet loom to obtain triazine modified high-strength polyester fiber fabric.
[0029] Example 2: S1: Add 100g of carbon fiber to 100mL of acetone solvent, heat to 60℃, react for 12h, after the reaction is complete, sonicate for 5min, dry, and obtain degummed carbon fiber. S2: Add 100g of degummed carbon fiber to 1000g of 65% concentrated nitric acid solution, heat to 100℃, react for 130min, adjust pH to 7, add cyclotriphosphazene modified silane coupling agent, heat to 100℃, react for 3h, rinse with boiling water to obtain cyclotriphosphazene modified silane coupling agent modified carbon fiber. S3: Mix 580g of polyether polyol YD-4110, 280g of YD-889, 100g of YD-204, and 150g of YD-380 evenly, add 35g of foam stabilizer DX-931 and 2.5g of antioxidant 1135, stir for 20-40 minutes to obtain component A; S4: Add 100g of polymethylene polyphenyl polyisocyanate to a beaker, heat to 70℃, preheat for 60min, and obtain component B; S5: Add 100g of component A and 100g of component B to a beaker, heat to 40℃, react for 3min, stir for 2min, then add 3g of cyclotriphosphazene-modified silane coupling agent to modify carbon fiber, heat to 50℃, cure for 70min, cool to 20℃, and let stand for 24h to obtain carbon fiber modified polyurethane film.
[0030] Example 3: S1: Under an argon atmosphere, 100g of hexachlorocyclotriphosphazene and 35g of hydroquinone were added to 150mL of tetrahydrofuran solvent and stirred until homogeneous. Then, 80g of triethylamine was added, the temperature was raised to 70℃, and the reaction was stirred for 50h. After the reaction was completed, the temperature was lowered and cooled, filtered, and the mixture was distilled under reduced pressure and recrystallized to obtain intermediate 3. S2: Add 45g of paraformaldehyde to 200mL of tetrahydrofuran solvent, add 45g of CaH2, heat to 20℃, react for 30min, then heat to 60℃, add 165g of N-[3-(trimethoxysilyl)propyl]ethylenediamine, heat to 80℃, add 100g of intermediate 3, react for 3h, filter, and distill under reduced pressure to obtain cyclotriphosphazene modified silane coupling agent.
[0031] Example 4: S1: Add 100g of tetrahydroxymethyl phosphonium sulfate to 150mL of diethylene glycol dimethyl ether solvent, heat to 25℃, add 50g of n-octadecyltrichlorosilane, heat to 60℃, react for 60min, heat to 130℃, react for 9h, cool, crystallize, filter, and obtain cage-like quaternary phosphate long-chain organosilicon ester. S2: Under a nitrogen atmosphere, 100g of hexamethylene diisocyanate and 1200g of polyether polyol LY-4110 were heated to 80℃ and reacted for 1.5h. The temperature was then lowered to 60℃, and 130g of chain extender diethylene glycol, 10g of catalyst stannous octoate, and 20g of dibutyl dilaurate were added. The mixture was reacted for 4h, and then 200g of isocyanate trimer, 60g of cage-like quaternary phosphate long-chain organosilicon ester, and 80g of chemically foamed microspheres were added. The mixture was stirred evenly, heated to 120℃, and reacted for 2h to obtain silane long-chain modified polyurethane foam.
[0032] Example 5: S1: 30g of modified polyurethane foam was calcined with a propane-oxygen mixed flame, heated to 800℃, with a flame sweeping time of 3s / time and a melting depth ≤0.1mm to obtain flame-activated foam. S2: Coat 35g of modified high-strength polyester fiber fabric with 3g of polyurethane hot melt adhesive, then align 20g of modified polyurethane film, place it on a hot press roller, heat to 110℃, pressure 1MPa, roller speed 3m / min to obtain pre-composite fabric. S3: Align and bond 30g of flame-activated foam with 58g of pre-composite fabric, let stand for 3 seconds, then place it on a hot press roller, heat to 50℃, pressure 1.5MPa, roller speed 10m / min to obtain wear-resistant and tear-resistant foam flame composite fabric.
[0033] Example 6 S1: 35g of modified polyurethane foam was calcined with a propane-oxygen mixed flame, heated to 900℃, with a flame sweeping time of 2s / time and a melting depth ≤0.1mm to obtain flame-activated foam. S2: Coat 4g of polyurethane hot melt adhesive onto 40g of modified high-strength polyester fiber, then align 25g of modified polyurethane film, place it on a hot press roller, heat to 120℃, pressure 0.8MPa, roller speed 4m / min to obtain pre-composite fabric. S3: Align and bond 35g of flame-activated foam with 69g of pre-composite fabric, let stand for 4s, then place on a hot press roller, heat to 40℃, pressure 1.8MPa, roller speed 7m / min to obtain wear-resistant and tear-resistant foam flame composite fabric.
[0034] Example 7 S1: 40g of modified polyurethane foam was calcined with a propane-oxygen mixed flame, heated to 1000℃, with a flame sweep time of 1s / time and a melt depth ≤0.1mm, to obtain flame-activated foam. S2: Coat 45g of modified high-strength polyester fiber with 5g of polyurethane hot melt adhesive, then align 30g of modified polyurethane film, place it on a hot press roller, heat to 130℃, pressure 0.5MPa, roller speed 5m / min to obtain pre-composite fabric. S3: Align and bond 40g of flame-activated foam with 80g of pre-composite fabric, let stand for 5s, then place on a hot press roller, heat to 30℃, pressure 2MPa, roller speed 5m / min to obtain wear-resistant and tear-resistant foam flame composite fabric.
[0035] Comparative Example 1: Compared with Example 5, this comparative example does not use the flame activation process, but directly uses the conventional hot pressing process to composite foam and fabric. The remaining steps and parameters are the same, and will not be repeated in this comparative example. Finally, wear-resistant and tear-resistant foam composite fabric is obtained.
[0036] Comparative Example 2: Compared with Example 5, this comparative example only replaces "ordinary polyester fiber fabric" with "triazine modified high-strength polyester fiber fabric". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, wear-resistant and tear-resistant foam flame composite fabric is obtained.
[0037] Comparative Example 3 Compared with Example 5, this comparative example only replaces "ordinary polyurethane film" with "carbon fiber modified polyurethane film". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, wear-resistant and tear-resistant foam flame composite fabric is obtained.
[0038] Comparative Example 4 Compared with Example 5, this comparative example only replaces "ordinary polyurethane foam" with "silane long-chain modified polyurethane foam". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a wear-resistant and tear-resistant foam flame composite fabric is obtained.
[0039] Comparative Example 5 Compared with Example 5, this comparative example only replaces "silane coupling agent KH-550" with "cyclotriphosphazene modified silane coupling agent". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, abrasion-resistant and tear-resistant foam flame composite fabric is obtained.
[0040] Performance testing: Abrasion resistance test According to GB / T21196.3-2007 "Textiles - Martindale Abrasion Resistance Test", the abrasion resistance of Examples 5-7 and Comparative Examples 1-5 was tested and analyzed using a Martindale abrasion tester. The sample holder weighs 200g, and the weights weigh 395g. The effective diameter of the friction head is 38.0±0.5mm, and the abrasive is standard wool abrasive. Before testing, the samples are placed in the test environment in a relaxed state for more than 18 hours. Then, three groups of 50×50mm samples are respectively... 2 Samples from Examples 5-7 and Comparative Examples 1-5 were placed in a clamp and subjected to wear resistance tests. During the test, the test was paused every 1000 wear resistance cycles, the clamp was removed, and the debris on the sample and abrasive surface was gently cleaned with a brush. The test was then continued until obvious holes appeared in the sample. The value on the reading dial was recorded at this time, and the average value of the three groups of samples was taken as the wear resistance cycle number of the sample.
[0041] Interface peel strength test According to the test standard GB / T2792-2014 "Test Method for Peel Strength of Adhesives", the 180° peel method was adopted, and the interfacial peel strength of the composite materials of Examples 5-7 and Comparative Examples 1-5 was tested using an AG-1 universal testing machine. The clamping distance was 100 mm, the tensile speed was 100 mm / min, the width of the sample was 25 mm, and the maximum peel force (N) was recorded.
[0042] Tear resistance test The test was conducted using a universal testing machine in accordance with GB / T3917.3-2009, "Textiles - Tear Properties - Part 3: Determination of Tear Strength of Trapezoidal Specimens". Grip spacing: 50mm, sample length: 120mm, sample width: 50mm, tensile speed: 100mm / min. Warp and weft tests were performed on Examples 5-7 and Comparative Examples 1-5 respectively. At least 5 valid data points were obtained for each sample, and the average value of the data used for analysis was taken.
[0043] Table 1. Detection data of Examples 5-7 and Comparative Examples 1-5
[0044] Limiting Oxygen Index (LOI) Test According to the test standard GB / T5455—1997 "Test for Burning Performance of Textiles - Oxygen Index Method", the limiting oxygen index was measured using a limiting oxygen index meter HC-2C. The burning performance of Examples 5-7 and Comparative Examples 1-5 was determined and analyzed, and the average of the five measurement results was taken.
[0045] Table 2 Limiting oxygen index detection data of Examples 5-7 and Comparative Examples 1-5
[0046] Performance testing after damp heat aging The samples from Examples 5-7 and Comparative Examples 1-5 were cut to fit into 15cm×15cm pieces, ensuring no creases or damage. The samples were then suspended in an ESPEC model constant temperature and humidity test chamber, avoiding contact between them. The temperature was set to 70℃ and the humidity to 95%RH, and the test was continued for 72 hours. After the test, the samples were removed and allowed to equilibrate in a laboratory environment for 24 hours. Then, the peel strength test and tear resistance test were performed.
[0047] Table 3 Mechanical test data after aging of Examples 5-7 and Comparative Examples 1-5
[0048] Antibacterial test Refer to the People's Republic of China Textile Industry Standard: Fz / r01021—1992 Test Method for Antibacterial Properties of Fabrics; The experimental bacterial suspension was directly dropped onto the fabric to be tested, allowing the bacteria to fully contact and be exposed on the fabric for a certain period of time. Then, the culture medium was placed over the fabric to allow the remaining bacteria to grow. The percentage decrease in bacterial count of the antibacterial sample was compared to determine its antibacterial ability. Colony-forming units were counted using a magnifying glass. The operating steps are as follows: 1. Preparation of bacterial culture: Take a 24-hour fresh broth culture of Escherichia coli, shake well, let stand for 20 minutes, and dilute to a bacterial count of 102. 5 -106 CFU / mL bacterial suspension; 2. Inoculation: Place the samples of Examples 5-7 and Comparative Examples 1-5, each measuring 5.0cm × 5.0cm, into a sterile Petri dish with a diameter of 9cm. Add 1.5mL of bacterial solution evenly, ensuring that it is evenly distributed and completely absorbed on the sample. Repeat each sample 6 times and place them in an incubator at 37℃ to dry for 1 hour. 3. Place the dried contaminated sample flat on the surface of a nutrient agar plate, then evenly cover the surface of the contaminated sample with semi-solid nutrient agar to a moderate thickness, and incubate in a 37% incubator for 48 hours. Set up a blank control group. 4. Observation results: Safran staining solution was added to the semi-solid nutrient agar above and stained for 1 hour. The number of colonies on each cloth sample was counted using a magnifying glass. The average number of colonies on 6 cloth samples was calculated and recorded. 5. Calculate the antibacterial rate: Repeat the above experiment three times, take the average value, and calculate the antibacterial rate using the following formula:
[0049] In the formula: A is the average colony count of the control cloth sample; B represents the average colony count of the antibacterial fabric sample.
[0050] Table 4. Antimicrobial activity test data of Examples 5-7 and Comparative Examples 1-5
[0051] Data Analysis: As can be seen from Tables 1-4, the wear-resistant and tear-resistant foam flame composite fabric prepared by the present invention has better wear resistance, tear resistance, flame retardancy, resistance to damp heat aging and antibacterial properties. In contrast, Comparative Example 1, which did not use the flame activation process, suffered a decrease in abrasion resistance and a weaker interfacial bond. Furthermore, after humid heat aging, its mechanical properties decreased significantly. This is because flame activation can improve the durability of the fabric, and unactivated foam is prone to moisture entering the bonding interface in a humid heat environment, which leads to easy delamination. At the same time, the flame activation process melts the foam surface, forming a stronger physical entanglement with polyester fibers and carbon fiber films. Comparative Example 2 uses ordinary polyester fibers, which leads to a decrease in its tear resistance. This is because the rigid ring structure of the triazine modified fibers disperses stress and avoids local tearing; the physical entanglement of the silane long-chain foam enhances the overall toughness. Comparative Example 3 showed lower peel strength due to the use of ordinary polyurethane film. This was because the cyclotriphosphazene-modified silane coupling agent significantly enhanced the interfacial bonding by bonding the carbon fiber and the polyurethane matrix through multiple active sites, and flame activation further optimized the adhesion between the foam and the fabric. Comparative Example 4 showed a decrease in LOI and antibacterial rate due to the use of ordinary foam. The reason is that the cage-like quaternary phosphate salt in the silane long-chain foam decomposes when exposed to fire to generate a phosphate barrier layer, which works in conjunction with carbon fiber to improve flame retardancy, and the quaternary phosphate salt structure enhances antibacterial durability. Comparative Example 5 showed a decrease in peel strength and antibacterial rate due to the use of silane coupling agent KH-550. This was because the cage-like quaternary phosphate long-chain organosilicon ester inhibited microbial adhesion, and its quaternary phosphate structure enhanced antibacterial durability. The long chain could enhance the cross-linking between the bonding interfaces. Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0052] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
Claims
1. A wear-resistant and tear-resistant foam flame-retardant composite fabric, characterized in that, The product comprises the following components in parts by weight: 35-45 parts modified high-strength polyester fiber fabric, 20-30 parts modified polyurethane film, 30-40 parts modified polyurethane foam, and 3-5 parts polyurethane hot melt adhesive. The modified high-strength polyester fiber fabric is a triazine-modified high-strength polyester fiber fabric; The modified polyurethane film is a carbon fiber modified polyurethane film; The modified polyurethane foam is a silane long-chain modified polyurethane foam. The triazine-modified high-strength polyester fiber fabric is prepared by the following method: Step A1: Add cyanuric chloride, 4-(ethylene oxide-2-ylmethyl)benzene-1,2-diol, sodium hydroxide, and deionized water to acetone solvent, stir and react for 3-5 hours, filter, and distill under reduced pressure to obtain intermediate 1; Step A2: Add intermediate 1 to tetrahydrofuran solvent, mix well, then add 6-amino-1-hexanol, heat to 20-30℃, stir for 10-14h, and after the reaction is complete, distill under reduced pressure to obtain intermediate 2. Step A3: Mix intermediate 2 with terephthalic acid, heat to 220-240℃, react for 2-4 hours, add the catalyst tetrabutyl titanate, vacuum to 40-50 Pa, heat to 250-260℃, react for 1-2 hours, then heat to 270-280℃, react for 3-5 hours. After the reaction is complete, cool and granulate to obtain polyester chips. Step A4: Dry the polyester chips, put them into a spinning machine, heat them to 300-320℃, filter them, extrude them with a twin-screw extrusion pressure of 4-5MPa and a winding speed of 700-900m / min, then stretch them with a stretching machine with a total stretch ratio of 4-5, and weave them with an air-jet loom to obtain triazine modified high-strength polyester fiber fabric. The carbon fiber modified polyurethane film is prepared by the following method: Step B1: Add carbon fiber to acetone solvent, heat to 50-60℃, react for 10-14 hours, after the reaction is complete, sonicate for 3-7 minutes, dry to obtain degummed carbon fiber. Step B2: Add the degummed carbon fiber to a 65% concentrated nitric acid solution, heat to 80-100℃, react for 110-130 min, adjust the pH to 7, add the cyclotriphosphazene-modified silane coupling agent, heat to 90-110℃, react for 1-3 h, rinse with boiling water, and obtain cyclotriphosphazene-modified silane coupling agent-modified carbon fiber. Step B3: Mix polyether polyols YD-4110, YD-889, YD-204, and YD-380 evenly, add foam stabilizer and antioxidant, and stir for 20-40 minutes to obtain component A; Step B4: Add polymethylene polyphenyl polyisocyanate to a beaker, heat to 50-70℃, preheat for 50-70 min, and obtain component B; Step B5: Add component A and component B to a beaker, heat to 30-50℃, react for 2-4 minutes, stir for 1-3 minutes, then add carbon fiber modified with cyclotriphosphazene-modified silane coupling agent, heat to 50-60℃, cure for 50-70 minutes, cool to 20-30℃, and let stand for 22-26 hours to obtain carbon fiber modified polyurethane film; The modified polyurethane foam is prepared as follows: Step D1: Add tetrahydroxymethyl phosphonium sulfate to diethylene glycol dimethyl ether solvent, heat to 20-25℃, add n-octadecyltrichlorosilane, heat to 50-60℃, react for 50-70 min, heat to 120-140℃, react for 8-10 h, cool, crystallize, filter, and obtain cage-like quaternary phosphate long-chain organosilicon ester; Step D2: Under a nitrogen atmosphere, hexamethylene diisocyanate and polyether polyol LY-4110 are heated to 70-80℃ and reacted for 1-3 hours. The temperature is then lowered to 50-60℃, and chain extender diethylene glycol, catalyst stannous octoate and dibutyl dilaurate are added. The reaction is continued for 3-5 hours. Isocyanate trimer, cage-like quaternary phosphate long-chain organosilicon ester and chemically foamed microspheres are added. The mixture is stirred evenly and heated to 110-130℃ for 1-3 hours to obtain silane long-chain modified polyurethane foam. The preparation method of the wear-resistant and tear-resistant foam flame composite fabric includes the following preparation steps: Step S1: The modified polyurethane foam is calcined with a propane-oxygen mixed flame, heated to 800-1000℃, with a flame sweeping time of 1-3s / time and a melting depth ≤0.1mm, to obtain flame-activated foam. Step S2: Coat the modified high-strength polyester fiber fabric with polyurethane hot melt adhesive, then align the modified polyurethane film, place it on a hot press roller, heat to 110-130℃, pressure 0.5-1MPa, roller speed 3-5m / min, to obtain the pre-composite fabric. Step S3: Align and bond the flame-activated foam with the pre-composite fabric, let stand for 3-5 seconds, then place it on a hot press roller, heat to 30-50℃, pressure 1.5-2MPa, roller speed 5-10m / min, to obtain abrasion-resistant and tear-resistant foam flame-composite fabric.
2. The abrasion-resistant and tear-resistant foam flame-reinforced composite fabric according to claim 1, characterized in that, The mass ratio of cyanuric chloride, 4-(ethylene oxide-2-ylmethyl)benzene-1,2-diol, sodium hydroxide, and deionized water in step A1 is 1:4-4.2:1.2-1.4:5.5-6; The mass ratio of intermediate 1 to 6-amino-1-hexanol in step A2 is 1.8-2:1; The mass ratio of intermediate 2 to terephthalic acid in step A3 is 4-5:
1.
3. The abrasion-resistant and tear-resistant foam flame-reinforced composite fabric according to claim 1, characterized in that, In step B2, the mass ratio of the degummed carbon fiber, concentrated nitric acid solution, and cyclotriphosphazene-modified silane coupling agent is 1:9-11:0.02-0.
04. In step B5, the mass ratio of component A, component B, and carbon fiber modified by cyclotriphosphazene-modified silane coupling agent is 1:1.0-1.2:0.02-0.
04.
4. The abrasion-resistant and tear-resistant foam flame-reinforced composite fabric according to claim 1, characterized in that, The cyclotriphosphazene-modified silane coupling agent is prepared as follows: Step C1: Under an argon atmosphere, hexachlorocyclotriphosphazene and hydroquinone were added to tetrahydrofuran solvent and stirred until homogeneous. Triethylamine was added, and the temperature was raised to 65-75℃. The mixture was stirred for 45-50 hours until the reaction was complete. The mixture was then cooled, filtered, distilled under reduced pressure, and recrystallized to obtain intermediate 3. Step C2: Add paraformaldehyde to tetrahydrofuran solvent, add CaH2, heat to 20-30℃, react for 20-40 min, then heat to 50-70℃, add N-[3-(trimethoxysilyl)propyl]ethylenediamine, heat to 75-85℃, add intermediate 3, react for 2-4 h, filter, and distill under reduced pressure to obtain cyclotriphosphazene modified silane coupling agent.
5. The abrasion-resistant and tear-resistant foam flame-reinforced composite fabric according to claim 4, characterized in that, The mass ratio of hexachlorocyclotriphosphazene, hydroquinone, and triethylamine in step C1 is 1:0.33-0.37:0.80-0.83; In step C2, the mass ratio of paraformaldehyde, CaH2, N-[3-(trimethoxysilyl)propyl]ethylenediamine to intermediate 3 is 0.43-0.47:0.45-0.49:1.65-1.70:
1.
6. The abrasion-resistant and tear-resistant foam flame-reinforced composite fabric according to claim 1, characterized in that, The mass ratio of tetrahydroxymethylphosphoric acid sulfate to n-octadecyltrichlorosilane in step D1 is 1:0.50-0.53; The mass ratio of hexamethylene diisocyanate, polyether polyol LY-4110, diethylene glycol, stannous octoate, dibutyl dilaurate, isocyanate trimer, cage-like quaternary phosphate long-chain organosilicon ester, and chemically foamed microspheres in step D2 is 1:12-14:1.3-1.5:0.1-0.3:0.1-0.2:2-4:0.5-0.7:0.7-0.9.
Citation Information
Patent Citations
Manufacturing process of low-VOC (volatile organic compound) functional automotive interior fabric
CN116512609A
Preparation process and application of double-color fabric
CN118639376A